Lean Six Sigma to increase operational efficiency in a coal mining company, Cajamarca 2024 - Goicochea Limay, Amy Nicole Stefania; Guevara Malca, Araceli Elizabeth; Miñan Olivos, Guillermo Segundo (LACCEI, 2024)
The research proposes the Lean Six Sigma methodology to improve operational efficiency in a coal mining company in Cajamarca, 2024. This applied study adopts a quantitative approach, with a non-experimental, descriptive, and cross-sectional design. It thoroughly analyzes operational efficiency, identifying key areas for improvement through tools such as Pareto charts, Ishikawa diagrams, and FMEA, along with Lean Six Sigma. Critical issues in processes, equipment maintenance, training, and operational standards are highlighted, with specific solutions proposed. Furthermore, production and efficiency over a specific period are evaluated, emphasizing the impact of identified issues on productivity and product quality. Lean Six Sigma tools were assessed under the uncertainty of effectiveness, using the Laplace criterion and sensitivity analysis, showing a high likelihood of economic benefits even under adverse scenarios. It concludes that Lean Six Sigma could significantly increase operational efficiency in the coal mining sector.